Morphological and nutritional study of hot air dried (Bio-dehydation system) oyster mushroom (Pleurotus sajor-caju) - Wan Rosli, W. I.; Aishah, M. S.; Nik Fakurudin,, N. A.; Mohsin, S. S. J. (Microscopy Society of Singapore, 2011)
Edible mushrooms have been widely consumed as food or food ingredients in different prepared food items in a long period. The choice of selecting this fungus is because of their antifungal, antioxidative properties and for their ability to reduce hypercholesterolemia and the posession of high radical scavenging activity.